Research on test method of elevator wire rope under special environment. Issue 5 (January 2021) - Xue, Zhaoling; Chang, Xiaoqing; Feng, Shuangchang; Fang, Liang; Liu, Yuming
Abstract: In order to analyze the influence of different special environment on the fatigue performance of elevator wire rope, this paper refers to the existing bending fatigue test method of wire rope, and other standard to simulate different environment conditions, a test method of elevator wire rope in special environment is presented in order to study the fatigue life and scrap condition of elevator wire rope in special environment.